THE IMMERSION EFFECT OF 50% KASTURI (Mangifera casturi) LEAF EXTRACT ON COLOR CHANGES OF THERMOPLASTIC NYLON DENTURE BASE - Dinda Nur Rusyida; Rahmad Arifin; Muhammad Yanuar Ichrom Nahzi (FKG Unlam, 2023)
ABSTRACTBackground: The most commonly used denture cleanser is alkaline peroxide. Long-term use of alkaline peroxide caused color change on denture base. One of which can be used as an alternative ingredient is kasturi leaf (Mangifera casturi). 50% kasturi leaf extract has antifungal properties against candida albicans. 50% kasturi leaf extract can be used as an alternative natural denture cleanser. Purpose: To know the immersion effect in 50% kasturi leaf extract on color changes of thermoplastic nylon. Methods: This study was true experimental with pretest dan posttest with control group design. 24 samples used simple random sampling with 8 samples in each groups. The sample is round sized 20mm in diameter and 3mm thickness. The treatment divided into 3 group, 50% leaf extract as treatment group, alkaline peroxide as positive control group, dan aquadest as negative control group. The color change was measured before and after immersion for five days using digital analysis tools with CIELab system. Results: One Way ANOVA dan Post Hoc Bonferroni statistical test showed significant differences (p<0,05) between the immersion groups in 50% kasturi leaf extract (6,25 ± 1,90), alkaline peroxide (4,00 ± 0,99), and aquadest (2,19 ± 0,71). Conclusion: The 50% kasturi leaf extract has effect on color changes of thermoplastic nylon denture base. The color changes in 50% kasturi leaf extract is higher than alkaline peroxide and aquadest. Keywords : Color changes, Kasturi leaf, Thermoplastic nylon